Small-Angle Scattering from Confined and Interfacial Fluids Applications to Energy Storage and Environmental Science - Melnichenko, Yuri B.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book examines the meso- and nanoscopic aspects of fluid adsorption in porous solids using a non-invasive method of small angle neutron scattering (SANS) and small angle x-ray scattering (SAXS). Starting with a brief summary of the basic assumptions and results of the theory of small-angle scattering from porous media, the author focuses on the practical aspects and methodology of the ambient and high pressure SANS and SAXS experiments and corresponding data analysis. It is illustrated with results of studies of the vapor and supercritical fluid adsorption in porous materials published during the last decade, obtained both for man-made materials (e.g. porous fractal silica, Vycor glass, activated carbon) and geological samples (e.g. sandstones, shales, and coal). In order to serve the needs of broad readership, the results are presented in the relevant context (e.g. petroleum exploration, anthropogenic carbon capture and sequestration,  ion adsorption in supercapacitors, hydrogen storage, etc.).
Basic definitions and essential concepts of small-angle scattering -- Radiation sources -- Constant flux and time-of-flight instrumentation -- Sample environment -- Practical aspects of planning and conducting SAS experiments -- Fundamentals of data analysis -- Structural characterization of porous materials using SAS -- Neutron and x-ray porosimetry -- Individual liquids and liquid solutions under confinement -- Supercritical fluids in confined geometries.
Keywords: Materials -- Analysis; Measurement; Measuring instruments; Spectrum analysis; Catalysis; Geotechnical engineering; Cogeneration of electric power and heat; Fossil fuels; Characterization and Analytical Technique; Measurement Science and Instrumentation; Spectroscopy; Catalysis; Geotechnical Engineering and Applied Earth Sciences; Fossil Fuel